2015
DOI: 10.1186/s12913-015-0964-3
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the magnitude and cause of geographic variation in unplanned hospital admission rates and length of stay for ambulatory care sensitive conditions

Abstract: BackgroundUnplanned hospital admissions place a large and increasing strain on healthcare budgets worldwide. Many admissions for ambulatory care sensitive conditions (ACSCs) are thought to be preventable, a belief supported by significant geographic variations in admission rates. We conducted a systematic review of the evidence on the magnitude and correlates of geographic variation in ACSC admission rates and length of stay (LOS).MethodsWe performed a search of Medline and Embase databases for English languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
91
0
11

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 64 publications
3
91
0
11
Order By: Relevance
“…The mean and median LOS across Europe were higher than expected from previous studies in individual countries around Europe [10, 26] and showed great variability. This is in keeping with a recent systematic review that showed consistently high variability of COPD LOS across countries in Europe, North America and Australasia [27]. The variability observed in the present study was, however, reduced when the hospital cluster effect (an important consideration in reducing bias from intrinsic institutional factors not measured in the analysis [24]) was accounted for.…”
Section: Discussionsupporting
confidence: 91%
“…The mean and median LOS across Europe were higher than expected from previous studies in individual countries around Europe [10, 26] and showed great variability. This is in keeping with a recent systematic review that showed consistently high variability of COPD LOS across countries in Europe, North America and Australasia [27]. The variability observed in the present study was, however, reduced when the hospital cluster effect (an important consideration in reducing bias from intrinsic institutional factors not measured in the analysis [24]) was accounted for.…”
Section: Discussionsupporting
confidence: 91%
“…Other cluster detection studies using Alberta data have focused on different conditions. [16][17][18][19][20] Although geographic variation in admission rates or length of stay has been identified in multiple studies for ambulatorycare-sensitive conditions, 21 many investigators did not con- Note: CI = confidence interval, COPD = chronic obstructive pulmonary disease, OR = odds ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Marked variations in outcomes for patients with respiratory disease have also been shown, regionally and between individual general practitioner (GP) practices 1. There is evidence linking the quality of care provided in general practice with unplanned admissions to secondary care,11 and decreased admission rates have been reported in a number of long-term conditions (including COPD and asthma) where GPs were financially incentivised to provide high-quality care 12. Moreover, higher levels of professional education, nurse staffing and clinical recording in primary care are all associated with an improvement in the quality of clinical care for patients with COPD 13.…”
Section: Introductionmentioning
confidence: 99%